Blind Spots in Law (2014)
Semiotic study of the law makes it possible to incorporate the notion of Peircean interpretation into legal logic, thereby adding a temporary category. Looking at the legal areas (which are large enough to hold their own general principles, and therefore do not have gaps stemming from lack of foresight about new technologies or situations that could involve the presence of gaps while considering an isolated standard; and suffiently defied so as not to generalize or become a closed system by defiition, which could signify the absence of gaps considered as a total legal system), it is possible to consider the law not as an integrity but as an integration , carried out through the successive incorporation of the diffrent branches of law throughout history, with diffrent notions about the subjects and objects worthy of their attention.Successive incorporation, although not organic, can cause fisures in its assembly, thus generating blind spots. Ths analysis thus leads to the need to investigate the binding process or reason for the diverse areas of the law.